When the Principal Is the Firm’s Problem: Principal Costs and Their Corporate Governance Implications - Zajac, Edward J.; Goranova, Maria (Academy of Management Review, 2026)
While agency theory has long dominated corporate governance research, we suggest that the common transplanting of the dyadic principal–agent problem into the corporate context has blurred key differences between principals and the firm as an entity. We redress this imbalance by advancing a conceptual framework of principal costs vis-à-vis the firm. We first show how principal costs can exist even in the single-principal corporate context, based on owner consumption and competence characteristics, which allows us to also distinguish principal costs from both agency costs and principal–principal expropriation costs. We then extend our principal costs theory to the multi-principal context, in which we highlight how principal costs, including private benefits of influence, can exist even in corporations with no controlling shareholder enjoying private benefits of control. In this latter context, we redirect the agency theoretic lens of incentive and informational concerns toward active minority shareholders whose actions generate principal costs vis-à-vis the firm, as well as passive shareholders who fail to constrain such principal costs. We conclude with a discussion of the broader implications of our theory for current and future corporate governance research, practice, and public policy.